Performance of the Arabic Population on the Adolescent-Adult Sensory Profile: An Observational Study [Corrigendum] - Al-Momani F (Dove Medical Press, 2020)
Al-Momani F, Alghadir AH, Al-Momani MO, et al. Neuropsychiatr Dis Treat. 2020;16:35–42.The authors have advised that the Acknowledgment section is incorrect. The correct acknowledgment is below.AcknowledgmentsThe authors are grateful to the Deanship of Scientific Research, King Saud University for funding through Vice Deanship of Scientific Research Chairs. This study was approved by the Deanship of Research at Jordan University of Science and Technology and Institutional Review Board of King Abdullah University Hospital, Irbid, Jordan.The authors apologize for this error.Read the original article